Effects of the mycotoxin metabolite de‐epoxy‐deoxynivalenol (DOM‐1) on embryo development and sperm motility in cattle. Issue 8 (2nd November 2020) - Guerrero‐Netro, Hilda M.; Barreta, Marcos H.; Costa, Eduardo; Goetten, Andre; Dupras, Raynald; Mills, Louis; Koch, Julia; Portela, Valério M.; Price, Christopher A.; Chorfi, Younes
Abstract: Contamination of animal feed with Fusarium spp results in accumulation of mycotoxins including deoxynivalenol. In animals, deoxynivalenol is metabolized to de‐epoxy deoxynivalenol (DOM‐1), which is generally considered to be a non‐toxic metabolite; however, recent studies demonstrated that DOM‐1 can reduce steroid production and induce apoptosis in the bovine ovary. The objectives of this study were to assess the effects of DOM‐1 on applied aspects of reproductive function in cattle, specifically sperm function and embryo development in vitro and follicle growth and superovulatory responses in vivo. The effect of naturally contaminated feed on superovulatory responses was assessed; a dose of 6 ppm deoxynivalenol increased blood DOM‐1 concentrations to 20 ng/ml, but this did not alter the number of viable embryos recovered on day 7. However, intrafollicular injection of DOM‐1 (100 ng/ml) directly into the growing dominant follicle resulted in cessation of follicular growth over the subsequent 3 days. Treatment with DOM‐1 reduced motility of bull spermatozoa over a 10‐h period in vitro. Addition of DOM‐1 to oocytes in vitro during IVM did not alter rates of cumulus expansion and nuclear maturation, but treatment during IVF reduced the rate of blastocyst formation. These data illustrate that DOM‐1 is more biologically active than previously thought and negatively impacted reproductive outcomes in cattle. Abstract : Deoxynivalenol is metabolized to de‐epoxy deoxynivalenol (DOM‐1) in ruminants, and DOM‐1 is generally considered to be non‐toxic. However, it appears to affect the reproductive system. Injection of DOM‐1 decreased ovarian follicle growth in cattle in vivo, and in vitro exposure had a negative impact on bovine sperm function and embryo development. These studies show that DOM‐1 has a negative effect on fertility in cattle.